Planos estaduais de educação e trabalho docente na educação básica: estudo sobre as metas de carreira e a remuneração dos estados de Amapá, Pará e Roraima (2015-2020) - SILVA, Levi Silva (UNIFAP – Universidade Federal do Amapá, 2022)
This study deals with the State Education Plans with regard to teaching work in Basic Education. The general objective of this research aims to investigate which conception of teaching work underlies the State Education Plans of Amapá, Pará and Roraima, with regard to career and remuneration. Therefore, its specific objectives are: a) Discuss the interfaces between the State Education Plans and the National Education Plan (PNE-2014-2024), with regard to the concepts of teaching work; b) Distinguish the different repercussions that the discourses of international organizations and the State Reform provoke in the educational policy that deals with teaching work in the aspect of career and remuneration, and c) Locate the career and remuneration of teachers in the states of Amapá, Pará and Roraima in the context of the tripod: international documents, National Education Plan and State Education Plans. The theme is imperative, as it brings together several considerations about the initiatives that the government has taken, with regard to the valuation of education professionals in the Amazon context. The current scenario of educational policy exposes a context of contradictions, uncertainties, cuts and restrictions in the financial contribution destined to public education, as well as attacks on the rights of teaching workers with social losses and setbacks within the scope of neoliberal society. The debate reinforces the discussion around the influence of the guidelines of international bodies such as the Organization for Economic Cooperation and Development (OECD), the World Bank (WB) and the United Nations Educational, Scientific and Cultural Organization (UNESCO), front to current educational policies. Given this scenario, a relevant question emerges: considering the influences of international organizations in the elaboration of the Brazilian Education Policy and the union struggles against the removal of workers' rights from Education, what conception of teaching work underlies the State Education Plans of Amapá, Pará and Roraima, with regard to career and remuneration? The work initially developed from a literature review to later consolidate itself as a documental research with a quantitative/qualitative approach, whose technique used for data interpretation is content analysis. In this perspective, the discussion constitutes a critical study that makes use of Dialectical Historical Materialism as a basic theory to support the proposed debate. The research results showed that different conceptions related to teaching work such as accountability, precariousness, proletarianization and professionalization are present in the documents of the state education plans of Amapá, Pará and Roraima, exposing the alignment of these policies to capital, through their commitment with the neoliberal education project. Therefore, there is a strong influence of international organizations on educational policies in the three states surveyed, with regard to remuneration and teaching career.